The change in the name of the Institute of Library and Information Science and its effect on the enrollment of new students to the Institute - Bajo, Roderick J. (2005)
The Institute of Library Science (ILS) adapted its new name, Institute of Library and Information Science (ILIS), on August 29, 2002 upon the approval of the Board of Regents at its 1162nd meeting. Before the Institute changed its name to ILIS, it has been lobbying to change its status from an Institute to a College and for it to be called the college of Library and Information Studies (CLIS). However, due to the low enrollment rate of students in the Institute, the petition of the Institute for it to be upgraded to College status was declined.